Untargeted Plasma Metabolomics and Gut Microbiome Profiling Provide Novel Insights into the Regulation of Platelet Reactivity in Healthy Individuals - Vadaq, Nadira; Schirmer, Melanie; Tunjungputri, Rahajeng N.; Vlamakis, Hera; Chiriac, Cecilia; Ardiansyah, Edwin; Gasem, M. Hussein; Joosten, Leo A. B.; de Groot, Philip G.; Xavier, Ramnik J.; Netea, Mihai G.; van der Ven, Andre J.; de Mast, Quirijn (Thrombosis and Haemostasis, 2021)
Background Considerable variation exists in platelet reactivity to stimulation among healthy individuals. Various metabolites and metabolic pathways influence platelet reactivity, but a comprehensive overview of these associations is missing. The gut microbiome has a strong influence on the plasma metabolome. Here, we investigated the association of platelet reactivity with results of untargeted plasma metabolomics and gut microbiome profiling.Methods We used data from a cohort of 534 healthy adult Dutch volunteers (the 500 Functional Genomics study). Platelet activation and reactivity were measured by the expression of the alpha-granule protein P-selectin and the binding of fibrinogen to the activated integrin αIIbβ3, both in unstimulated blood and after ex vivo stimulation with platelet agonists. Plasma metabolome was measured using an untargeted metabolic profiling approach by quadrupole time-of-flight mass spectrometry. Gut microbiome data were measured by shotgun metagenomic sequencing from stool samples.Results Untargeted metabolomics yielded 1,979 metabolites, of which 422 were identified to play a role in a human metabolic pathway. Overall, 92/422 (21.8%) metabolites were significantly associated with at least one readout of platelet reactivity. The majority of associations involved lipids, especially members of eicosanoids, including prostaglandins and leukotrienes. Dietary-derived polyphenols were also found to inhibit platelet reactivity. Validation of metabolic pathways with functional microbial profiles revealed two overlapping metabolic pathways (“alanine, aspartate, and glutamate metabolism” and “arginine biosynthesis”) that were associated with platelet reactivity.Conclusion This comprehensive overview is an resource for understanding the regulation of platelet reactivity by the plasma metabolome and the possible contribution of the gut microbiota.
Keywords: metabolome; microbiome; platelet; platelet reactivity